2022
DOI: 10.3389/fnmol.2022.927195
|View full text |Cite
|
Sign up to set email alerts
|

Decreased anterograde transport coupled with sustained retrograde transport contributes to reduced axonal mitochondrial density in tauopathy neurons

Abstract: Mitochondria are essential organelle required for neuronal homeostasis. Mitochondria supply ATP and buffer calcium at synaptic terminals. However, the complex structural geometry of neurons poses a unique challenge in transporting mitochondria to synaptic terminals. Kinesin motors supply mitochondria to the axonal compartments, while cytoplasmic dynein is required for retrograde transport. Despite the importance of presynaptic mitochondria, how and whether axonal mitochondrial transport and distribution are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…It implies an interaction between α-Syn pathology and diminishing levels of kinesins in PD. In addition, as kinesin motors supply mitochondria to the axonal compartments and synapses, the reduction in kinesin levels further led to impaired anterograde axonal transport of mitochondria and ATP deficit in human iPSC (induced pluripotent stem cell)-derived PD neurons carrying α-Syn gene duplication ( Prots et al, 2018 ; Sabui et al, 2022 ). The understanding of pathological mechanisms of reducing kinesin expression in facilitating restoration of anterograde transport will improve spatial abnormal distribution and dysfunction of mitochondria in PD.…”
Section: Axonal Transport Defects In Neurodegenerative Diseasesmentioning
confidence: 99%
“…It implies an interaction between α-Syn pathology and diminishing levels of kinesins in PD. In addition, as kinesin motors supply mitochondria to the axonal compartments and synapses, the reduction in kinesin levels further led to impaired anterograde axonal transport of mitochondria and ATP deficit in human iPSC (induced pluripotent stem cell)-derived PD neurons carrying α-Syn gene duplication ( Prots et al, 2018 ; Sabui et al, 2022 ). The understanding of pathological mechanisms of reducing kinesin expression in facilitating restoration of anterograde transport will improve spatial abnormal distribution and dysfunction of mitochondria in PD.…”
Section: Axonal Transport Defects In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Metabolism and Tau pathology mutually influence the function of each other through the p38 MAPK pathway [50] and through the ability of Tau to alter mitochondria directly [57,61,62] . As such clear links are present between metabolism, cognitive dysfunction, and Tau pathology, OXPHOS and aerobic glycolysis are currently undervalued therapeutic avenues that could offer impactful treatment options for targeting Tau and amyloid-beta pathology alone.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous physical links between Tau and mitochondria have been made. Mutant Tau has been shown to impair mitochondrial axonal transport in AD mouse models and human induced pluripotent stem cells (iPSCs) [57,58] ; human Tau (hTau) expression impairs mitochondrion fusion and fission in Drosophila and mouse neurons, and hTau mice [59,60] ; hTau or mutant Tau reduces mitochondrial quality control through mitophagy in N2a cells and C. elegans neurons [61] ; and mutant Tau directly reduces the mitochondrial membrane potential required for ATP-synthesis in triple transgenic mice [62] , or iPSC-derived neurons from people with Tau mutation causing frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17) [63] .…”
Section: Tau and Oxphosmentioning
confidence: 99%
“…Using different experimental settings, the authors were able to verify that Aβ’s effects on mitochondrial transport involve glycogen synthase kinase 3beta (GSK3β) signaling [ 108 ], a kinase with proven involvement in Aβ-induced anterograde axonal transport deficits through its interaction with kinesin light chains [ 109 ]. More recently, it was demonstrated that the overexpression of tau P301L in primary neurons inhibited kinesin recruitment to mitochondria, thus inhibiting the anterograde mitochondria’s movement towards the axon terminals [ 110 ]. Notably, the retrograde transport of mitochondria was not affected by P301L [ 110 ].…”
Section: Mitochondria (Dys)function In Alzheimer’s Disease: a Brief O...mentioning
confidence: 99%
“…More recently, it was demonstrated that the overexpression of tau P301L in primary neurons inhibited kinesin recruitment to mitochondria, thus inhibiting the anterograde mitochondria’s movement towards the axon terminals [ 110 ]. Notably, the retrograde transport of mitochondria was not affected by P301L [ 110 ]. In fact, several data suggest the increased vulnerability of the anterograde axonal mitochondrial transport in comparison with the opposite retrograde movement in AD-related conditions [ 103 ].…”
Section: Mitochondria (Dys)function In Alzheimer’s Disease: a Brief O...mentioning
confidence: 99%